Muskox body temperature and activity data - Schmidt, Niels Martin (Zenodo, 2019)
Data on muskox ( Ovibos moschatus ) body temperature (°C) and activity (count) from Zackenberg in Northeast Greenland collected every 4 hours during the period from autumn 2017 to summer 2018.